Effectiveness and safety of ablative fractional CO2 laser for the treatment of burn scars: A case-control study. Issue 4 (June 2021) - Issler-Fisher, Andrea C.; Fisher, Oliver M.; Haertsch, Peter A.; Li, Zhe; Maitz, Peter K.M.
Highlights: 167 patients treated with the AFL-CO2 were compared with 20 patients receiving standard scar management in a nested case-control study. Regardless of scar maturation status, the AFL-CO2 treatment group showed significant improvement in scar thickness and scar associated symptoms. Burn specific quality of life increased significantly in the AFL-CO2 group, but worsened at the follow up of the patients receiving standard care. Complications only occurred in 5 patients (2.9%) treated with AFL-CO2 and were generally mild in nature. Burn scars can be effectively and safely treated with the AFL-CO2 and this treatment induces profound improvements in relevant burn patient outcomes. Abstract: Background: Burn scars are a major clinical challenge. The aim of this study was to determine the effectiveness and safety of one treatment with the ablative fractional CO2 laser (AFL-CO2 ) compared to standard burn scar treatment. Method: From December 2014 to October 2018 patients were prospectively recruited and treatment effects analyzed by assessing various outcome parameters from the date of first consultation and after treatment. A case control study was conducted looking at the impact of one AFL-CO2 treatment compared to a cohort subjected to conventional conservative treatment. Adverse effects were noted at follow up. Results: 187 patients were included, with 167 in the AFL-CO2, and 20 in the control cohort. Baseline demographics and scar characteristics showed no significant differences. Ultrasound measured scar thickness as well as the Vancouver Scar Scale (VSS) revealed a significant reduction in the treatment cohort, but no significant improvement in the control group. The POSAS-O was significantly improved in both cohorts. Subjective parameters (POSAS-P, DN4-Pain, and modified D4Pruritus scores) decreased significantly in the AFL-CO2 cohort but remained unchanged in the control group. The BSHS-B quality of life score increased significantly in the AFL-CO2 group, but worsened at the follow up of the untreated patients. Sub-domain analyses found the biggest differences in Affect, Body Image, Heat Sensitivity, Treatment and Work. Complications occurred in 5 patients (2.9%). Conclusions: This study demonstrates that AFL-CO2 is an effective and safe treatment modality for burn scars improving thickness, symptoms and quality of life of burn survivors when compared to conventional scar treatment.